The essential rose garden the practical guide to growing, care and maintenance of roses - McHoy, Peter (Lorenz Book, 1998)
For anyone who loves to garden with roses, this book not merely a celebration of their beauty and versatility, but a treasure trove of information, practical advice and innovative rose garden design.